Analisis Kelayakan Usahatani Cabai Keriting (Capsicum Annum L) di Erik Farm Desa Ladogahar Kecamatan Nita Kabupaten Sikka - Theresia Dua Martha; Sarlina Noni (Peneliti.net, 2022)
Curly Chili Plant (Capsicum annum L.) is a horticultural commodity in Indonesia that is widely consumed by the community. Chili plants are classified as perdu plants from the eggplant family that has the scientific name Capsicum sp. Chili plants have several benefits including: curly chili contains many carbohydrates as a source of human energy, rich in vitamin C, and vitamin B1, there is also a healthy fat content that is good for the body. This study was conducted to find out: factors that affect the production of curly chilies, the income level of curly chili farming and the feasibility of curly chili farming business in Erik Farm Ladogahar Village Nita District Sikka. The data analysis used in this study is quantitative and qualitative with the data source used i.e. primary and secondary data. The results of this study showed that the curly chili farming business in Erik Farm Ladogahar Village, Nita District, Sikka Regency, experienced a profit of Rp 61,200,000 in one growing season. The R /C value of curly chili farming business in Erik Farm Ladogahar Village, Nita District of Sikka Regency is 2.09, meaning that the production of curly chili plant farming in Erik Farm Ladogahar Village, Nita District, Sikka Regency is worth trying